1997
DOI: 10.1515/cclm.1997.35.8.597
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin - Influence of Temperature, Storage, Anticoagulation and Arterial or Venous Asservation of Blood Samples on Procalcitonin Concentrations

Abstract: In this study we have analysed the influence of temperature and time of storage and of repeated freezing on procalcitonin plasma concentrations ex vivo. We have also analysed the difference of procalcitonin concentrations in arterial or venous blood samples and the influence of different anticoagulation techniques on procalcitonin concentrations (serum, EDTA-, lithium-heparin-or citrate plasma). At room temperature (25 °C) a loss of procalcitonin plasma concentrations of 6.4% ± 2.6% (mean, 2 standard error of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 3 publications
0
51
0
5
Order By: Relevance
“…Its serum level starts to increase 4-6 hours after the beginning of inflammation. The serum level is parallel to the degree of tissue damage (33). In studies in which CRP levels were evaluated by focus of infection in febrile neutropenia, Fleischhack et al (34) found that CRP levels were significantly higher in subjects with Gram-negative bacteremia compared with the FUO group, and similar to the subjects with CDIs.…”
Section: Discussionmentioning
confidence: 99%
“…Its serum level starts to increase 4-6 hours after the beginning of inflammation. The serum level is parallel to the degree of tissue damage (33). In studies in which CRP levels were evaluated by focus of infection in febrile neutropenia, Fleischhack et al (34) found that CRP levels were significantly higher in subjects with Gram-negative bacteremia compared with the FUO group, and similar to the subjects with CDIs.…”
Section: Discussionmentioning
confidence: 99%
“…PCT values have been reported as various levels: in bacterial infections with systemic findings as sepsis up to 1,000 ng/ ml, in localized infections, viral infections and inflammation reactions except infections mostly below 5 ng/ml, in patients with serious bacterial infections between 20 and 200 ng/ml and in normal populations like blood donors between 0 and 0.5 ng/ml [18,19]. CRP is one of the acutephase proteins and many studies are designed to compare it.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo koşullarda çok stabil bir protein olup, yarılanma süresi 25-30 saat kadardır. Oda ısısında stabil olması, sıcağa, donmaya ve erimeye dayanıklı olması ve basit laboratuvar tekniklerinin mevcut olması tanımlanmasını kolaylaştırır (10,11,21). Sağlıklı bireylerde PCT'nin plazma konsantrasyonları pikogram kadar düşük düzeylerdedir ve mevcut PCT ölçüm yöntemlerinin belirleyebileceği düzeylerin altındadır (<0.1 ng/ml).…”
Section: İrdelemeunclassified